Attitudes toward consumer involvement in mental health services: a cross-sectional survey of Indian medical and nursing undergraduates - Poreddi, Vijayalakshmi; Gandhi, Sailaxmi; Thimmaiah, Rohini; BM, Suresh (Investigación y Educación en Enfermería, 2016)
Objective. To understand the views of medical and nursing undergraduates regarding consumer involvement in mental health services. Methods. A descriptive cross sectional survey was conducted in Bangalore, South India, among medical (n=155) and nursing (n=116) undergraduates using self-reported the Mental Health Consumer Participation Questionnaire of Happell et al. “Mental health consumer” or “consumer” is defined as a person who is currently using mental health services as either an in-patient or out-patient. Results. The overall mean score on Mental Health Consumer Participation Questionnaire (54.1±6.7) implies that 64% of the participants hold positive attitudes towards consumer involvement in mental health services. Medical students possessed more positive attitudes than nursing in: consumer capacity (p<0.001), consumer as staff (p< 0.001) and overall score on mental health consumer participation questionnaire (t=6.892, p<0.001). Conclusion. The findings suggest that majority of the participants hold positive attitudes towards mental health consumer involvement in health care services. However, additional research is urgently required from developing countries to understand the effectiveness of involving mental health consumers in academic programs at undergraduate level. How to cite this article: Poreddi V, Gandhi S, Thimmaiah R, Suresh BM. Attitudes toward consumer involvement in mental health services: a cross-sectional survey of Indian medical and nursing undergraduates. Invest. Educ. Enferm. 2016; 34(2):